Comparison among zooplankton communities in hydrologically different lentic ecosystems - Stephan, Ligia Roma [UNESP]; Castilho-Noll, Maria Stela Maioli [UNESP]; Henry, Raoul [UNESP] (Asociacion Iberica de Limnologia, 2017)
Marginal lagoons in wetlands, which differ from artificial reservoirs, are subject to water level significant variations and can provide a high diversity of zooplankton. This study sought to determine whether communities of cladocerans and copepods differ in terms of richness, density and food preferences in small artificial reservoirs andmarginal lagoons,which have different hydrological regimes and connections with other aquatic environments. During the dry and rainy seasons, samples were taken from a set of 12 small artificial reservoirs in the northwestern region of the São Paulo state (Brazil) and in six marginal lagoons of the Paranapanema River wetland in the southeastern region of the São Paulo state (Brazil). We found a greater richness of zooplankton species (observed and estimated) in lagoons than in reservoirs. The species composition was significantly different in both ecosystems, and only cladocerans were more abundant in the lagoons. Although lagoons presented higher gamma diversity than reservoirs, the lagoons had lower beta diversity, reflecting the environment connections in wetlands to organisms' dispersion. Filter feeders were the most abundant group in both type of environment, but significant differences were observed in omnivores capturing prey, which were denser in reservoirs than in lagoons. The comparison between both kinds of ecosystem showed that zooplanktonic community differs in relation to the richness, density and trophic guild. We suggest that the influence of the hydrodynamics in lagoons, provided by lateral river connections, represents an important force in the aquatic community structuration, resulting in higher species diversity. This study evidences that ecosystems that are subject to connections with other aquatic environments and to water level variations can provide a higher diversity of aquatic communities, and that this kind of ecosystem are important to preserve the aquatic biodiversity.
Keywords: Cladocera; Copepoda; floodplain; function groups